Measuring vapour pressure with an isoteniscope - a hands-on introduction to thermodynamic concepts - Brechtelsbauer,C; Haslam,A; Shah,U; Macey,A; Chen,W (Journal of Chemical Education, 2016)
Characterization of the vapor pressure of a volatile liquid or azeotropic mixture, and its fluid phase diagram, can be achieved with an isoteniscope and an industrial grade digital pressure sensor using the experimental method reported in this study. We describe vapor-pressure measurements of acetone and n-hexane and their azeotrope, and how the data can be used to calculate thermodynamic properties of the test liquids, such as the molar heat of vaporization. This hands-on experience allows students to appreciate important thermodynamic concepts such as phase equilibrium, preparing them for more advanced studies of the subject.